Chemical Study and Evaluation of Antibacterial and Antioxidant Activities of Kombucha Variation Gel with Strawberry (Fragaria vesca) Extract and Ashoka Flower (Ixora coccinea L.) Extract - Goldha Faroliu; Kony Putriani; Yessi Rahayu; Nanda Rahma Tri Cahyaningrum; Mardiatul Jannah (Biology, Medicine, & Natural Product Chemistry, 2026)
Kombucha is a fermented drink made from tea, sugar, yeast, and acetic acid bacteria known as SCOBY (Symbiotic Culture of Bacteria and Yeast). Ashoka flowers (Ixora coccinea L.) are tropical ornamental plants rich in polyphenols that have antioxidant activity. Strawberries (Fragaria vesca) contain flavonoids that can inhibit bacterial growth by disrupting DNA processes, damaging cell membranes, and denaturing proteins in bacteria. This research was making gel preparations that actively inhibit bacterial growth. Examples of pathogenic bacteria include S. aureus and S. epidermidis which generally attack the skin, and its antioxidant activity.  The research was making kombucha tea with a combination of strawberries and Ashoka flowers, making gel preparations, testing activity against S. aureus, S. epidermidis, and Methilen Resistant Staphylococcus aureus (MRSA) bacteria, and testing antioxidant activity using the FRAP method. Gel with Fermented Tea (Kombucha) Combination of Strawberries and Ashoka Flowers has antibacterial activity against S. aureus bacteria in the strong category in Formula F3 (MIC 10.9 mm), against S. epidermidis bacteria in the moderate category in Formula F3 (MIC 9.06 mm), and against MRSA bacteria in the moderate category in Formula F3 (MIC 9.51 mm). Formulation F3 has antioxidant activity in the very strong category (47.32 mgAAE/g). Kombucha contains Phenol and Acid content that can damage bacterial cell walls. The addition of Strawberries and Ashoka flowers containing phenolic and flavonoid compounds increases the antibacterial and antioxidant activity of the gel.